First steps with React : get started building React apps fast (O'Reilly, 2017)
"React is a JavaScript library used to create complex user interfaces for the web, native applications, and virtual reality. React allows developers to create large applications that use data and can change over time without reloading the page. In this quick introductory course, you'll learn everything you need to know to get started with React. You'll discover a painless way to set up a React project and then you'll use React to build a working star rating UI component (i.e., the classic rating system where users rate things on a scale of one to x stars). Along the way, you'll see how React treats components as functions (functions that simply return UI elements); you'll learn how to create components and nest them inside other components (and why that's useful); you'll explore 'state' (one of React's most import concepts) and how it relates to the way components display data that changes over time; and you'll finish up by learning how to manage complex state data with React's setState and array mapping tools."--Resource description page